Immunity in athletes - MacKinnon, L. T. (International Journal of Sports Medicine, 1997)
There is a general perception among athletes, coaches and sports physicians that athletes are susceptible to infectious illness, such as upper respiratory tract infection (URTI), during intensive training and major competition; recent epidemiological evidence is consistent with this perception. Recent studies have focused on the effects of exercise on immune parameters in order to better understand mechanisms by which exercise training may influence resistance to infection. Intensive exercise has been shown to transiently alter a number of immune parameters including circulating leukocyte and subset numbers, plasma cytokine concentrations, natural killer cell activity, secretory immunoglobulin A secretion rate, and neutrophil and macrophage phagocytic activity. Many of these changes persist for several hours or even days after intensive exercise. Some athletes have been shown to exhibit low resting or postexercise values on some nonspecific immune parameters compared with clinical norms, such as complement, acute phase proteins, and neutrophil activation. In addition, extended periods of intensive exercise training have been associated with progressive decreases in some immune parameters such as neutrophil function and certain subclasses of serum and secretory immunoglobulin. These data suggest the possibility of clinically relevant immune suppression in well-trained athletes. Psychological stress associated with training and competition at the elite level may be an additive factor to the effects of intensive exercise on immune function.